The territorial structure of productive forces of Russian North-West in the 2000-2010s - Martynov, Vasily L.; Sazonova, Irina Ye. (Baltic Region, 2013)
A number of researchers are studying regional specifications of Russia from a variety of different perspectives. Economic geography has developed its own methods of approaching the study of territories, and looks, in particular, at geographical distribution of labour. In this article, we use the framework provided by this discipline to describe the changes in the economy of the Russian North-West in the first decade of the 21st century. We combine publicly available data to propose new methods of evaluation of regional economic efficiency. We also identify and describe new trends of North- West development that have not yet been reflected upon by the researchers in the field. We conclude that, having overcome the crisis of the 1990s, the economy of the Russian North- West displays an overall positive trend of coming back to the territorial structures of the beginning of the 20th century.